Co-seismic deformation for the 2015 MW7.8 Gorkha earthquake (Nepal) using near-field GPS data - Jing Xiong; Chao Chen; Jiaming Cao; Junxiang Wang; Xingbo Liu (Geodesy and Geodynamics, 2023)
Seasonal variations and common mode errors affect the precision of the Global Positioning System (GPS) time series. In this paper, we explore to improve the precision of coordinate time series, thereby providing a better detection of weak or transient deformation signals, particularly co-seismic signals. Based on 97 GPS stations, including the campaign and continuous GPS stations in Nepal and southern Tibet, we first consider seasonal variations and common errors, then obtain co-seismic deformation of the 2015 Gorkha earthquake in Nepal and southern Tibet. Our co-seismic rupture model is characterized by a shallow ramp and a deeper detachment fault, in agreement with the relocated aftershock sequence. Our results indicate that the earthquake rupture is mainly distributed in the upper-crustal fault, and the maximum slip is up to 8.0 m at ∼15.0 km depth located in the approximate-80 km east of the epicenter. The average slip is more than 5 m, and the total modelled magnitude is MW7.84, consistent with the observed seismic moment. Our rupture model for the 2015 Gorkha earthquake suggests that the rupture zone is not only in the upper crustal Main Himalayan Thrust (MHT), but also spreads to the northern segment of the MHT.